The Influence of the Flipped Classroom-Based Adaptive Learning System on Student Learning Outcomes in Science Subjects at SMP Negeri 3 Ma'rang - Muminang Muminang; Andi Adam; Wahyudin Wahyudin (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the impact of an adaptive learning system based on the flipped classroom model on the learning outcomes of ninth-grade students in Natural Sciences at SMP Negeri 3 Ma'rang. Using a quasi-experimental design, the research compared an experimental group employing adaptive flipped learning with a control group using conventional methods. The results showed a significant increase in posttest scores for the experimental group (mean = 84.83) compared to the control group (mean = 69.25). The adaptive learning model encouraged personalized learning experiences and fostered student engagement. The normalized gain (N-Gain) of 43.6% for the experimental group indicates high effectiveness of the method.